2017
DOI: 10.1016/j.envint.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Investigating causal relation between prenatal arsenic exposure and birthweight: Are smaller infants more susceptible?

Abstract: Background Shortening of gestation and intrauterine growth restriction (IUGR) are the two main determinants of birthweight. Low birthweight has been linked with prenatal arsenic exposure, but the causal relation between arsenic and birthweight is not well understood.. Objectives We applied a quantile causal mediation analysis approach to determine the association between prenatal arsenic exposure and birthweight in relation to shortening of gestation and IUGR, and whether the susceptibility of arsenic exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…We used data from a prospective birth cohort established in Bangladesh during 2008–2011. The details of this study, including details of recruitment and enrollment have been previously reported (13). Briefly, women were eligible to participate if they were ≥18 years old with an ultrasound confirmed singleton pregnancy of ≤16 weeks’ gestation; used a tube well as their primary source of drinking water; had been using the same drinking water source for >6 months; and intended to live in her current residence throughout pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from a prospective birth cohort established in Bangladesh during 2008–2011. The details of this study, including details of recruitment and enrollment have been previously reported (13). Briefly, women were eligible to participate if they were ≥18 years old with an ultrasound confirmed singleton pregnancy of ≤16 weeks’ gestation; used a tube well as their primary source of drinking water; had been using the same drinking water source for >6 months; and intended to live in her current residence throughout pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we observed that the effect of miR-1290 on birthweight was stronger when the arsenic concentration was higher in cord blood. In utero arsenic exposure has been associated with increased risk of preterm birth [57] and lower birthweight [27] in this population. Therefore, higher expression of miR-1290 in the placenta could potentially influence birthweight via shortened gestational age and increased arsenic toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…During 2008-2011, we enrolled 1,613 pregnant women aged ≥ 18 years with an ultrasound-confirmed singleton pregnancy of ≤ 16 weeks of gestation and followed them throughout pregnancy. Details of this study, including recruitment and enrollment criteria were previously reported [25,27]. At the end of follow-up, 1,184 singleton live births were recorded after exclusions due to loss of contact before delivery (n = 99), participation withdrawal (n = 121), miscarriage (n = 132), stillbirth (n = 72), and multiple pregnancies (n = 5).…”
Section: Study Population and Subject Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediation analyses can help uncover mechanisms of action that may explain the association between environmental exposures and perinatal health outcomes (Anthopolos et al, 2014;Ferguson et al, 2016;Rahman et al, 2017). In the present retrospective cohort study, we used stochastic direct and indirect effects (also called randomized interventional effects) (Rudolph et al, 2017;VanderWeele and Tchetgen Tchetgen, 2017) to evaluate maternal mental health during pregnancy as a potential mediator of a previously observed relationship between UNGD and adverse birth outcomes in Pennsylvania (Casey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%